แนวทางการดำเนินงานตามระบบประกันคุณภาพภายในเพื่อรองรับการประเมินคุณภาพภายนอกรอบสี่ ของสถานศึกษาขนาดเล็ก อำเภอฝาง จังหวัดเชียงใหม่ - จตุพร ชินะใจ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study has 2 objectives which are 1) to analysis for results the third External Quality Assessment of Small Educational Institutions, Fang District, Chiang Mai Province and 2) to study the guidelines for Internal Quality Assurance System Implementation for Supporting the Fourth External Quality Assessment of Small Educational Institutions, Fang District, Chiang Mai Province. There are 3 steps for this study which are 1) analysis for results of the third External Quality Assessment of Small Educational Institutions, Fang District, Chiang Mai Province. The datas source for this study were the 14 papers of the results third External Quality Assessment of Small Educational Institutions, Fang District, Chiang Mai Province, on 2014. The tools used in this study was analysis papers and the data was analyzed by using frequency average and sequence. 2) study and draft the guidelines of Internal Quality Assurance System Implementation for Supporting the Fourth External Quality Assessment of Small Educational Institutions, Fang District, Chiang Mai Province. The population for this study was the directors, teacher, person and supervisors who make for Internal Quality Assurance System of the school which were the total population of 15 people. The tool used for this study was interview and the data was analyzed by ช inductive inference. 3)examine the guidelines of Internal Quality Assurance System Implementation for Supporting the Fourth External Quality Assessment of Small Educational Institutions, Fang District, Chiang Mai Province. The populations for this study were the experts, the school administrators, the supervisor and the External Quality assessor which were the total population of 7 people. The tools used in this study were the examination form of possibility, suitability, and usefulness. The data was analyzed by using average and standard deviation. From the study, it found that the problem for Internal Quality Assurance System of Small Educational Institutions, Fang District, Chiang Mai Province in the score and quality are poor level. The distinctive point of the Small Educational Institutions, Fang District, Chiang Mai Province were a few for did by Ministerial regulations of Internal Quality Assurance System, on 2011.The weaknesses and the suggestion for found that problem of the information of IT. about Internal Quality Assurance System, so they should were systematize for planning and used the Technology when they did the Internal Quality Assurance System. The auditing result to study the guidelines for Internal Quality Assurance System Implementation for Supporting the Fourth External Quality Assessment of Small Educational Institutions, Fang District, Chiang Mai Province were matching for the flag of the Fourth External Quality Assessment and the possibility, suitability and usefulness about Guidelines for Internal Quality Assurance System Implementation for Supporting the Fourth External Quality Assessment of Small Educational Institutions, Fang District, Chiang Mai Province was in the highest level.